Henry VIII and Martin Luther : the second controversy, 1525-1527 - Rex, Richard; Henry VIII, King of England, 1491-1547 (The Boydell Press, 2021)
A modern critical edition of Henry VIII's second published work against Martin Luther. This open letter to Luther, printed at the king's command in December 1526, was in reply to a private letter addressed to him by Luther the previous year. Its particular interest lies in the fact that, unlike his better known Assertion of the Seven Sacraments, published five years before, Henry's open letter was released not only in Latin but also in an official Englishtranslation, with a special English preface added by the king for the edification of his subjects. This edition thus enables modern readers to hear what Henry had to say about Luther in his own words, and how he wanted his subjects to regard the German heresiarch. This critical edition is based on a previously unrecognised presentation manuscript which furnishes the earliest surviving text of both letters. In addition, it offers editions and newtranslations of a range of related texts, including Luther's reply to Henry and further contributions to the burgeoning controversy from several of the most prominent Catholic opponents of Luther in Europe. For Henry's letter, like his earlier book, became for a while a European sensation, reprinted in towns and cities from Cologne to Cracow. This fully annotated edition includes a substantial introduction which for the first time tells the full history of Henry's second controversy with Luther, and which sets that story in the broader context of the lengthy and fractious relationship between the two men from the time of Luther's emergence in 1517 until his death in 1546.